UPAYA GURU DALAM MENINGKATKAN ILMU TARTIL AL-QURAN DAN QIROATI PADA SISWA BUMRUNGSUKSA ISLAMIC BOARDING SCHOOL DI THAILAND (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to teachers’ efforts to improve students’ tartil Qur’an recitation through the implementation of the Qiroati method at Bumrungsuksa Islamic Boarding School in Southern Thailand. This study employed a Classroom Action Research (CAR) method conducted in three cycles, namely planning, action, observation, and reflection. The subjects of the study were Qur’an teachers and students involved in the Qur’an learning process using the Qiroati method. Data were collected through observation, tests of Qur’an reading ability, and documentation. The results of the study indicate that the implementation of the Qiroati method can improve students’ ability to read the Qur’an in a tartil manner. This improvement is reflected in the students’ learning outcomes in each cycle, increasing from 58% in the pre-cycle, to 68% in Cycle I, 78% in Cycle II, and reaching 88% in Cycle III. The improvement occurred because the learning process was conducted gradually through structured Qiroati levels, supported by individual guidance, regular reading practice, periodic evaluation, and learning motivation. Although several obstacles were encountered, such as differences in students’ initial abilities, limited instructional time, and language factors, teachers were able to overcome them through grouping students based on ability, providing additional practice, and utilizing audio media as a model for correct Qur’an recitation. Therefore, the Qiroati method is effective in improving students’ tartil Qur’an reading ability in accordance with tajwid rules.